PARTNERSHIP PATTERN AND HOUSEHOLD WELFARE LEVEL OF SUGARCANE FARMERS - Ashwini A (Global Journal of Plant and Soil Sciences, 2023)
Partnering with a sugar factory is the main choice for sugarcane farmers in Bone Regency because they are unable to process their own farm production, obtain market guarantees, and obtain production facilities. The aims of this study were to: (1) Identify the partnership pattern between sugarcane farmers and PT Perkebunan Nusantara XIV (PTPN XIV) Camming Sugar Factory, (2) Analyze the income of sugarcane farmers, (3) Analyze the welfare level of sugarcane farmers’ households. The respondents were 35 sugarcane farmers who had partnerships with PTPN XIV Camming Sugar Factory, and two key informants fromthe company who supervised the partnership which were expected to be able to provide information about the partnership pattern. The analytical method used is descriptive statistical analysis, income analysis, farmer’s household income structure analysis, household expenditure structure and welfare level analysis. The results showed that: (1) The partnership pattern run by sugarcane farmers and PTPN XIV Camming Sugar Factory isplasma-core pattern, where core being the nucleus and plasma the smallholding farmers. (2) The average income per harvest season of sugarcane farming is Rp. 13.991.923. (3) Sugarcane farmer households are categorized as prosperous with an average of 37.6% of total household expenditure is on food.